2015
DOI: 10.3892/or.2015.4421
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A gene mutation in ovarian and endometrial cancers (Review)

Abstract: The AT-rich interacting domain-containing protein 1A gene (ARID1A) encodes ARID1A, a member of the SWI/SNF chromatin remodeling complex. Mutation of ARID1A induces changes in expression of multiple genes (CDKN1A, SMAD3, MLH1 and PIK3IP1) via chromatin remodeling dysfunction, contributes to carcinogenesis, and has been shown to cause transformation of cells in association with the PI3K/AKT pathway. Information on ARID1A has emerged from comprehensive genome-wide analyses with next-generation sequencers. ARID1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 70 publications
4
127
0
Order By: Relevance
“…Furthermore, ARID1A mutations and BAF250a deficits were identified in OCCC and adjacent endometriotic lesions, but not in distant lesions, which suggests that this mutation and resultant BAF250a deficit are events in the early stage of neoplastic transformation of endometriosis (2,42). A previous study confirmed that an ARID1A deficit was also an early phenomenon in endometriosis-associated ovarian cancer (EAOC) and endometriotic ovarian cysts, together with AKT protein activation and a histone H2A variant (ÎłH2AX) (43).…”
Section: Aberrant Chromatin Remodeling and Ovarian Cancersupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, ARID1A mutations and BAF250a deficits were identified in OCCC and adjacent endometriotic lesions, but not in distant lesions, which suggests that this mutation and resultant BAF250a deficit are events in the early stage of neoplastic transformation of endometriosis (2,42). A previous study confirmed that an ARID1A deficit was also an early phenomenon in endometriosis-associated ovarian cancer (EAOC) and endometriotic ovarian cysts, together with AKT protein activation and a histone H2A variant (ÎłH2AX) (43).…”
Section: Aberrant Chromatin Remodeling and Ovarian Cancersupporting
confidence: 65%
“…In 22 patients with uterine CS, Jones et al (57) revealed ARID1A mutations in 8 (36%) cases, mutations of histone methyltransferase MLL3 in 6 (27%) cases, mutations of speckle-type POZ protein (SPOP), which is involved in chromatin remodeling, in 3 (14%) cases, and mutations of chromatin remodeling-associated genes in 14 (64%) cases (57). ARID1A serves an important role in the regulation of cell growth, and MLL3 is a coactivator of tumor protein p53 (TP53), a tumor suppressor p53 gene (2,58). SPOP is a transcriptional repressor of p53 via the bric-a-brac/tramtrack/broad complex protein (59).…”
Section: Aberrant Chromatin Remodeling and Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…22 Recently, it has also been suggested that ARID1A mutations may be targeted by EZH2 inhibitors that are currently in development. 23 Consequently, the first priority for further research in this molecular subtype is more extensive sequencing with methods such as whole-exome sequencing, RNA sequencing, and whole-genome sequencing to discover novel genomic events affecting kinases that could suggest therapeutic vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A knockout mice do not develop ovarian tumors, whereas 60% with a double ARID1A/PTEN knockout develop ovarian cancers. 24,25 Therefore, in AE and to a lesser extent typical endometriosis, critical molecular aberrations develop that predispose to cancer. Further research is needed to find biomarkers that identify patients with endometriotic lesions at high risk for developing EaOC.…”
Section: Discussionmentioning
confidence: 99%